2012
DOI: 10.1128/jb.06041-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Campylobacter jejuni RacRS Reveals Roles in the Heat Shock Response, Motility, and Maintenance of Cell Length Homogeneity

Abstract: bCampylobacter jejuni commensally colonizes the cecum of birds. The RacR (reduced ability to colonize) response regulator was previously shown to be important in avian colonization. To explore the means by which RacR and its cognate sensor kinase RacS may modulate C. jejuni physiology and colonization, ⌬racR and ⌬racS mutations were constructed in the invasive, virulent strain 81-176, and extensive phenotypic analyses were undertaken. Both the ⌬racR and ⌬racS mutants exhibited a ϳ100-fold defect in chick colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 79 publications
0
24
0
Order By: Relevance
“…Previous studies have demonstrated that the RacRS two-component system is important for C. jejuni to colonize chickens and that this system supports growth at 42°C (Bras et al, 1999) or above 42°C (Apel et al, 2012). Two genes, encoding a periplasmic cytochrome c peroxidase homologue Cj0358 (Bras et al, 1999) and dnaJ encoding a heat shock chaperone (Apel et al, 2012), have been reported to be regulated by RacR.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the RacRS two-component system is important for C. jejuni to colonize chickens and that this system supports growth at 42°C (Bras et al, 1999) or above 42°C (Apel et al, 2012). Two genes, encoding a periplasmic cytochrome c peroxidase homologue Cj0358 (Bras et al, 1999) and dnaJ encoding a heat shock chaperone (Apel et al, 2012), have been reported to be regulated by RacR.…”
Section: Figurementioning
confidence: 99%
“…So far two genes are known to be regulated by RacR, i.e. a periplasmic cytochrome c peroxidase homologue Cj0358 (Bras et al, 1999) and dnaJ encoding a heat shock chaperone (Apel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas DccRS directly influences expression of genes encoding colonization determinants (22), CprRS is required for expression of genes for biofilm formation (24). RacRS is required for expression of genes encoding proteins for the heat shock response and fumarate metabolism, depending on the strain and growth conditions used for analysis (25)(26)(27). Additionally, the PhosSR TCS is required for expression of 12 genes, 5 of which encode proteins required for phosphate acquisition (28).…”
mentioning
confidence: 99%
“…For instance, the FlgSR TCS monitors formation of the flagellar type III secretion system, the MS ring, and rotor structures to activate expression of 54 -dependent flagellar genes required for motility and commensal colonization (15)(16)(17)(18)(19)(20)(21). Furthermore, DccRS, CprRS, and RacRS are required for wild-type (WT) levels of commensal colonization of the chick ceca (22)(23)(24)(25)(26). Whereas DccRS directly influences expression of genes encoding colonization determinants (22), CprRS is required for expression of genes for biofilm formation (24).…”
mentioning
confidence: 99%
“…4). Thus, 5'-methylthioadenosine nucleosidase was found to play a key role in the futalosine pathway of H. pylori (i.e., chorismate / 6-amino-6-deoxyfutalosine / dehypoxanthinyl futalosine / cyclic dehypoxantine futalosine / 1,4-dihydroxy-6-naphthoic acid / MK) [29,30]. FAs have been shown to possibly inhibit a step after the formation of futalosine [24].…”
Section: Discussionmentioning
confidence: 97%